Selection and Morphological Characterization of Crossed Anthurium (Anthurium andreanum) cv. Midori × Angel - Ridho Kurniati; Suryawati Suryawati; Supenti Supenti; Riska Syafrina (The University of Lampung, 2024)
The floriculture industries depend on market and consumer preferences which dynamically change. Innovation to create new varieties is one of the solutions. The breeding program enhances genetic variation and new varieties. One of the methods was conventional cross breeding. The research objective was to characterize and select the potential clones in the F1 population of crossing anthurium cv. Midori × Angel. Anthurium Midori as female parent and Anthurium cv. Angel as male parent. The individual selection method was used to select the F1 population of Anthurium cv. Midori × Angel. The observation parameters were spathe length (cm), spadix length and width (cm), total number of leaves, total number of shoots, total number of flowers, inflorescent length (cm), and plant height (cm). There were 26 individual offspring from the crossing Anthurium cv. Midori × Angel. Most of the offspring inherited from both the combination of Midori and Angel. They were greenish white. Green was from Midori and white was from Angel. MA-16 and MA-27 were selected as potential clones to be registered as new varieties. The character of these clones was green spathe inherited from Midori as female parent. Keywords: Clone, Leaf color, Leaf shape, Offspring, Varieties.